# How do you factor and solve #6x^2 - 5x = 6#?

##### 2 Answers

#### Explanation:

First subtract

#6x^2-5x-6 = 0#

Factor using an AC method:

Find a pair of factors of

The pair

#0 = 6x^2-5x-6#

#=6x^2-9x+4x-6#

#=(6x^2-9x)+(4x-6)#

#=3x(2x-3)+2(2x-3)#

#=(3x+2)(2x-3)#

Hence zeros:

The solutions are the values of

#### Explanation:

By completing the square you can get the formula for the solutions (roots) of a 2nd degree polynomial equation

So the first solution is

Similarly, the second solution is